Peran Dokter Ahli Jiwa Dalam Proses Peradilan Untuk Menentukan Ketidakmampuan Bertanggung Jawab Pelaku Tindak Pidana (Studi Kasus Di Rumah Sakit Jiwa Daerah Surakarta) - Sanyoto, Thesa Tamara, Dr. Natangsa Surbakti, S.H., M.Hum (2016)
This study aims to determine the role of psychiatrists in the judicial process in determining the inability of responsible perpetrators of criminal acts, the status and legal force psychiatrists as Information Expert/Expert in criminal proceedings. The method used is empirical juridical with descriptive research. The data source consists of primary data is the result of interviews and secondary data is data of primary and secondary law. Data were collected by interview and observation and then analyzed qualitatively. The results showed that the role of psychiatrist doctor is important in the avoidance of doubt the law enforcement agencies in determining the mental state of the offender. Notch specialists psyche as one of the five legitimate evidence in accordance with Article 184 paragraph (1), while the legal force of a psychiatrist is just as consideration of judges, because that determines the perpetrators of the crime in a criminal or not is judge.